ANALISIS PENDAPATAN DAN NILAI TAMBAH EMPING TEKI PADA INDUSTRI RUMAH TANGGA DESA KERTASADA KABUPATEN SUMENEP - Eka Nofidayanti (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2015)
Through agro-industry, Teki processing can increase the value of Teki and increaserevenue. We conducted this study in order to determine the amount of revenue, income and added value obtained from the processing of Teki to chips by the home agri-industry in Kertasada village. The research methodology is done purposively by taking the data from the entire population. The reseach was in Kertasada Village Sumenep Regency with 20 people as population. The primary data obtained through interviews and secondary data from relevant agencies. The collected data were then analyzed for income and Hayami added value analysis. The results showed that the research are the profit level is RP 275.000 per year. R/C Ratio analysis resullt is 1,15 it shows that the bussiness of home agri-industry of rumput teki chips is already efficient, because 1,15 is greater than 1. ROI result is 0,15 it means that for every capital will gain return for 0,15. The value added that is achieved by the produser of home agri-industry of rumput teki chips is quite enough for every kilogram tuber will give a value added 25,210 or 75,9%. And BEP analysis is 43,29 it means that producer provitable if they can produce 43 packs per year.